Permanent makeup: a tattoo imitation procedure from the Shariah perspective - Musaddad, Nusaibah Anuar; Bakar, Elistina Abu; Zaidan, Uswatun Hasanah; Awang, Mohd Daud; Mohd Safian, Yasmin Hanani (Faculty of Syariah and Law, Islamic Science University of Malaysia (USIM), 2024)
The growing interest in permanent makeup, which provides a lasting and perfect appearance, has sparked concerns regarding its safety and compliance with Islamic beliefs. This study aims to elucidate the Shariah ruling on permanent makeup by employing a document analysis method to examine all relevant Shariah information, including Quranic verses, hadith, Islamic jurisprudence and fatwas. Consequently, this study examines the medical aspects of the procedure to gain a comprehensive understanding of the issue. This study employed document analysis to investigate permanent makeup procedures from both the medical and Shariah perspectives. The analysis of the Shariah perspective on tattoos and cosmetic procedures included a review of medical journals and websites addressing the practice, focusing on techniques, safety, and concerns associated with permanent makeup procedures. Additionally, fatwas concerning permanent makeup from Islamic scholars available on fatwa websites across the globe were analysed. This study concludes that Muslims should refrain from undergoing permanent makeup procedures because they involve skin penetration and the use of permanent pigments, making them comparable to tattoos, which are prohibited in Islam. This study on halal in cosmetic services adds to the existing body of knowledge in the halal industry, and pave the way for further research to be conducted on similar topics in the future.